2018
DOI: 10.15517/rbt.v66i3.31775
|View full text |Cite
|
Sign up to set email alerts
|

Morfogénesis de la fase sexual de los helechos epífitos Microgramma mortoniana y Pleopeltis macrocarpa (Polypodiaceae) reserva Natural Punta Lara, Buenos Aires, Argentina

Abstract: Sexual morphogenesis phase of the epiphytic ferns Microgramma mortoniana and Pleopeltis macrocarpa (Polypodiaceae) from Punta Lara Natural Reserve, Buenos Aires, Argentina. The Punta Lara Natural Reserve is located on the riverside of the La Plata River in the province of Buenos Aires, Argentina. It is the Southernmost relict in the world of subtropical riparian forest. The epiphytic ferns studied in this work belong to the Polypodiaceae family: Microgramma mortoniana and Pleopeltis macrocarpa. Plant communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Early gametophyte development stages of Cibotium barometz Gametophyte development of C. barometz in vitro culture is of the Drynaria-type (Nayar and Khaur 1969). The same type of gametophyte development is reported in Adiantum capillus-veneris L. (Oloyede et al 2017), Lepisorus nudus (Singh et al 2017), Microgramma mortoniana, and Pleopeltis macrocarpa (Gorrer et al 2018). As also described by Praptosuwiryo et al 2015, when at the fimentous stage (prothallus has 5-10 or more cells) one of the cells at the top margin of the prothallus (the anterior marginal cells) then divides obliquely across its width (Figure 1.C.).…”
Section: Spore Germination and Early Gametophyte Development Stages Osupporting
confidence: 73%
See 1 more Smart Citation
“…Early gametophyte development stages of Cibotium barometz Gametophyte development of C. barometz in vitro culture is of the Drynaria-type (Nayar and Khaur 1969). The same type of gametophyte development is reported in Adiantum capillus-veneris L. (Oloyede et al 2017), Lepisorus nudus (Singh et al 2017), Microgramma mortoniana, and Pleopeltis macrocarpa (Gorrer et al 2018). As also described by Praptosuwiryo et al 2015, when at the fimentous stage (prothallus has 5-10 or more cells) one of the cells at the top margin of the prothallus (the anterior marginal cells) then divides obliquely across its width (Figure 1.C.).…”
Section: Spore Germination and Early Gametophyte Development Stages Osupporting
confidence: 73%
“…Deng et al (2007) and Praptosuwiryo et al (2015) also reported only one type of spore germination of C. barometz, the Vittariatype. A similar types of spore germination also reported in Aglaomorpha cornucopia (Huang et al 2015), Lepisorus nudus (Singh et al 2017), Microgramma mortoniana and Pleopeltis macrocarpa (Gorrer et al 2018). Farfán-Santillán (2017) reported two types of germination of Gleichenia and Cyathea; and three types of prothallial development Marattia, Osmunda and Drynaria.…”
Section: Spore Germination and Early Gametophyte Development Stages Osupporting
confidence: 65%
“…Our studies in this area also included the reproductive aspects of some native ferns, as well as the analyzes of soil spore banks as contributions to biodiversity conservation in this area (Ramos Giacosa et al, 2014Luna et al, 2016;Ramos Giacosa et al, 2017;Gorrer et al, 2018).…”
mentioning
confidence: 99%
“…ex Willd. (Gorrer et al, 2018), Amauropelta Kunze, Christella H. Lév. and Goniopteris C. Presl (=Thelypteris Schmidel) (Giudice et al, 2014;Ramos Giacosa et al, 2014).…”
mentioning
confidence: 99%
“…As part of a project to ascertain on the reproductive biology of native ferns in Argentina (Luna et al, 2016;Ramos Giacosa et al, 2017;Gorrer, Berrueta, Ramos Giacosa, Giudice, & Luna, 2018), a fungus was found during in vitro spore culture of L. venustum. After examining the sporophytes with magnifying glass, dark brown spots and eruptive pustules were observed in fertile leaves.…”
mentioning
confidence: 99%